Australian Public Knowledge of Islam - Kevin M. Dunn (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2005)
This research outline the extent and nature of the australian peoples' knowledge of Islam. only the fifth of respondents had reasonable or better knowledge of Islam, and half knew a little about ISlam. Males, middle-aged (25-49) and older respondent (50+) were much more likely to claim a fragmentary or better knowledge of Islam. By far the greatest variation in knowledge of Islam was between those with and without some tertiary education.DOI: 10.15408/sdi.v12i1.644